Molecular Composition of Heterochromatin and Its Contribution to Chromosome Variation in the Microtus thomasi/Microtus atticus Species Complex - Rovatsos, Michail; Marchal, Juan Alberto; Giagia-Athanasopoulou, Eva; Sánchez, Antonio (Genes, 2021)
The voles of the Microtus thomasi/M. atticus species complex demonstrate a remarkable variability in diploid chromosomal number (2n = 38-44 chromosomes) and sex chromosome morphology. In the current study, we examined by in situ hybridization the topology of four satellite DNA motifs (Msat-160, Mth-Alu900, Mth-Alu2.2, TTAGGG telomeric sequences) and two transposons (LINE, SINE) on the karyotypes of nine chromosome races (i.e., populations with unique cytogenetic traits) of Microtus thomasi, and two chromosomal races of M. atticus. According to the topology of the repetitive DNA motifs, we were able to identify six types of biarmed chromosomes formed from either Robertsonian or/and tandem fusions. In addition, we identified 14 X chromosome variants and 12 Y chromosome variants, and we were able to reconstruct their evolutionary relations, caused mainly by distinct mechanisms of amplification of repetitive DNA elements, including the telomeric sequences. Our study used the model of the Microtus thomasi/M. atticus species complex to explore how repetitive centromeric content can alter from chromosomal rearrangements and can shape the morphology of sex chromosomes, resulting in extensive inter-species cytogenetic variability.
Keywords: telomeric sequences; Animals; telomery; Microtus; Telomere; heterochromatin; Heterochromatin; transpozibilní elementy DNA; Evolution, Molecular; molekulární evoluce; Arvicolinae; Genetic Variation; pohlavní chromozomy; Msat-160; DNA Transposable Elements; Sex Chromosomes; sex chromosomes heterochromatin; polymorphism; repeated DNAs; zvířata; genetická variace